2001
DOI: 10.1073/pnas.121034798
|View full text |Cite
|
Sign up to set email alerts
|

A larger hippocampus is associated with longer-lasting spatial memory

Abstract: Volumetric studies in a range of animals (London taxi-drivers, polygynous male voles, nest-parasitic female cowbirds, and a number of food-storing birds) have shown that the size of the hippocampus, a brain region essential to learning and memory, is correlated with tasks involving an extra demand for spatial learning and memory. In this paper, we report the quantitative advantage that food storers gain from such an enlargement. Coal tits (Parus ater) a food-storing species, performed better than great tits (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
103
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 24 publications
2
103
2
2
Order By: Relevance
“…The only attempts at comparing memory capacity between species of hoarding and non-hoarding birds have focused on working memory, which is believed to be a different system from long-term memory, at least in mammals (Rolls 2000;Squire 2004). In an operant touch-screen study in which they varied working memory duration (1 -30 s), capacity (one to four items) and accuracy (distance on the screen), Biegler et al (2001) found no evidence for a larger working memory capacity in coal tits compared with great tits.…”
Section: Using Ecology To Predict Specific Memory Adaptationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The only attempts at comparing memory capacity between species of hoarding and non-hoarding birds have focused on working memory, which is believed to be a different system from long-term memory, at least in mammals (Rolls 2000;Squire 2004). In an operant touch-screen study in which they varied working memory duration (1 -30 s), capacity (one to four items) and accuracy (distance on the screen), Biegler et al (2001) found no evidence for a larger working memory capacity in coal tits compared with great tits.…”
Section: Using Ecology To Predict Specific Memory Adaptationsmentioning
confidence: 99%
“…The fact that hoarding coal tits (Periparus ater) have a longer lasting working memory than non-hoarding great tits (Parus major) (Biegler et al 2001) does not speak directly to the duration of cache memories, although longer lasting working memory could translate into better memory consolidation and therefore potentially longer lasting long-term memories. compared coal tits and marsh tits (both hoarders) with blue tits (Cyanistes caeruleus) and great tits (both non-hoarders) on an avian analogue of the 8-arm radial arm maze at different retention intervals.…”
Section: Using Ecology To Predict Specific Memory Adaptationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A decade and a half later, however, it is not clear that that promise is being realised. For example, food storing, once a model for examining questions of the evolution of cognition and possibly the wildest of all the examples discussed in Balda et al (1998), is now much less of a focus (e.g., Biegler, McGregor, Krebs, & Healy, 2001;Hampton & Shettleworth, 1996;Sherry & Vaccarino, 1989; but see Feeney, Roberts, & Sherry, 2009;Freas, LaDage, Roth, & Pravosudov, 2012). Food storing did, however, lead to perhaps the greatest recent flurry of excitement and effort in comparative cognition (Clayton & Dickinson, 1999): the examination of cognitive abilities in corvids.…”
mentioning
confidence: 99%